Compromising Paradigm in the Dialectic of Islamic Civil Law and Customary Law in Central Kalimantan - Ariyadi, Ariyadi; Tanjung, Ardi Akbar; Dlaifurrahman, Muhammad; Susilo, Adib (International Tatho Academics, 2025)
This study aims to describe Islamic family law, Sharia economic law, and customary law in marriage and inheritance practices in Central Kalimantan. This study uses a descriptive qualitative approach with literature studies and normative-sociological studies. The research data sources consist of legislation, the Compilation of Islamic Law (KHI), Islamic economic law literature, and Dayak and Malay customary law documents. Data analysis is interpretative. The results of the study show that the three legal systems interact dynamically. In marriage, Islamic law emphasizes the pillars and requirements of sharia. Meanwhile, Dayak customs add rituals and marriage expenses. This integration becomes both religious and social legitimacy. In inheritance, Islamic law rigidly regulates distribution according to the Qur'an. Meanwhile, customary law emphasizes deliberation and equality. In this context, Sharia economic law provides room for grants or wills. This study emphasizes that the practice of Islamic civil law in Indonesia can be dynamic and contextual even in the midst of existing social, cultural, and state norms.